Factors Influencing International Tourists In Choosing A Travel Destinations : Case Study Of Penang, Malaysia - Ang, Lay Pooi (2006)
The aim of this paper is to define the elements that affect tourists in choosing a destination. Tujuan kajian ini adalah untuk menentukan faktor-faktor yang akan mempengaruhi pemilihan destinasi oleh pelancong asing.